2022
DOI: 10.1167/iovs.63.13.18
|View full text |Cite
|
Sign up to set email alerts
|

Different Murine High-Risk Corneal Transplant Settings Vary Significantly in Their (Lymph)angiogenic and Inflammatory Cell Signatures

Abstract: Purpose Pathologic conditions in the cornea, such as transplant rejection or trauma, can lead to corneal neovascularization, creating a high-risk environment that may compromise subsequent transplantation. This study aimed to evaluate the impact of different types of corneal injury on hemangiogenesis (HA), lymphangiogenesis (LA) and immune cell pattern in the cornea. Methods We used five different corneal injury models, namely, incision injury, alkali burn, suture place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Alkali burns have also been used as a modeling tool to induce inflammatory lymphangiogenesis. Zhang et al's experiments in the murine model of incision injury, alkali burn, suture placement, low-risk keratoplasty, and high-risk keratoplasty revealed that corneal alkali burns produced fewer nascent lymphatic vessels than suture and graft burn wounds but significantly more nascent lymphatic vessels than incision burns ( Zhang et al, 2022b ).…”
Section: Advances In Nascent Lymphatics In Multiple Ocular Diseasesmentioning
confidence: 99%
“…Alkali burns have also been used as a modeling tool to induce inflammatory lymphangiogenesis. Zhang et al's experiments in the murine model of incision injury, alkali burn, suture placement, low-risk keratoplasty, and high-risk keratoplasty revealed that corneal alkali burns produced fewer nascent lymphatic vessels than suture and graft burn wounds but significantly more nascent lymphatic vessels than incision burns ( Zhang et al, 2022b ).…”
Section: Advances In Nascent Lymphatics In Multiple Ocular Diseasesmentioning
confidence: 99%
“…Different methods of corneal injury can induce vastly different inflammatory profiles including various degrees of lymphangiogenesis [207]. Corneal alkali burns induce a relatively modest lymphangiogenic response compared to keratoplasty and suture placement but a stronger response than incision [207].…”
Section: Alkali Burnmentioning
confidence: 99%
“…Different methods of corneal injury can induce vastly different inflammatory profiles including various degrees of lymphangiogenesis [207]. Corneal alkali burns induce a relatively modest lymphangiogenic response compared to keratoplasty and suture placement but a stronger response than incision [207]. In a direct comparison between suture-induced and alkali burn-induced corneal inflammation, alkali burn produced a less pronounced lymphangiogenic response but a similar hemangiogenic response, indicating that differences in the method of induction of inflammation may be significant for corneal lymphangiogenesis [208].…”
Section: Alkali Burnmentioning
confidence: 99%